Coffee beverage reduces ROS production and does not affect the organism's response against Candida albicans - Alessandra dos Santos Danziger Silvério; Rosemary G. F. Alvarenga Pereira; Stella Maris da Silveira Duarte; Sônia Aparecida Figueiredo; Cláudia de Souza Ferreira; Adriene Ribeiro Lima; Fernanda Borges de Araújo Paula; Tomaz Henrique Araújo; Eric Batista Ferreira; Maria Rita Rodrigues (São Paulo State University (UNESP), 2020)
Coffee is a mixture of substances with potential beneficial and adverse health effects. Several studies demonstrate the antioxidant effect of the phenolics compounds present in coffee. Neutrophils produce reactive oxygen species (ROS) by activating NOX2, which plays a key role in organism defense against microbial pathogens. Diabetes mellitus patients are more susceptible to bacterial and fungal infections. The present study evaluated the influence of coffee beverage on NOX2 activity and ROS generation and the impact of this effect on phagocytosis and killing of Candida albicans by neutrophils from diabetic and non-diabetic animals. Diabetes was induced in male Wistar rats using 2% alloxan. Diabetic and non-diabetic animals were divided into groups treated and untreated with coffee drink (7.2 mL/kg/day) or apocyanine (16 mg/kg/day) for 50 days. After 50 days, the animals' glycemic profile was measured by blood glucose and HbA1c tests. The generation of ROS in neutrophilic cells was measured by chemiluminescence and cytochrome C reduction assays. C. albicans phagocytosis and death were evaluated by optical microscopy using the May-Grunwald-Giemsa staining method. The coffee drink has not altered the glycemic profile and NOX2 activity of the animals. However, coffee reduced the ROS pool in non-diabetic and diabetic animals, but this activity did not harm the phagocytosis or killing of neutrophils. Treatment with apocyanin decreased ROS production and killing capacity of neutrophils from non-diabetic animals against C. albicans. We suggest that the coffee drink intake prevents oxidative damage and does not impair response of the organism against opportunistic microorganism.